2017
DOI: 10.1186/s12920-017-0249-2
|View full text |Cite
|
Sign up to set email alerts
|

Gene and protein analysis reveals that p53 pathway is functionally inactivated in cytogenetically normal Acute Myeloid Leukemia and Acute Promyelocytic Leukemia

Abstract: BackgroundMechanisms that inactivate the p53 pathway in Acute Myeloid Leukemia (AML), other than rare mutations, are still not well understood.MethodsWe performed a bioinformatics study of the p53 pathway function at the gene expression level on our collection of 1153 p53-pathway related genes. Publically available Affymetrix data of 607 de-novo AML patients at diagnosis were analyzed according to the patients cytogenetic, FAB and molecular mutations subtypes. We further investigated the functional status of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 134 publications
0
11
1
Order By: Relevance
“…Previous studies have suggested that MDM4 mRNA levels are overexpressed in AML, 22,23 while variable results have been observed for mRNA expression levels of MDM2 and p53 in myeloid malignancies 19,21,22,25,31 . We found no significant difference in mRNA expression of MDM2 , p53 and MDM4 between AML, MDS and CMML samples and control samples.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Previous studies have suggested that MDM4 mRNA levels are overexpressed in AML, 22,23 while variable results have been observed for mRNA expression levels of MDM2 and p53 in myeloid malignancies 19,21,22,25,31 . We found no significant difference in mRNA expression of MDM2 , p53 and MDM4 between AML, MDS and CMML samples and control samples.…”
Section: Discussioncontrasting
confidence: 77%
“…20 The same discrepancies were observed for MDM4 and p53 protein expression and appeared to be largely due to the techniques, and possibly control samples used (Table 1). [17][18][19][20][21][22][23][24][25][26][27][28][30][31][32][33] After studies suggesting overexpression of MDM2 and MDM4, clinical trials have been conducted in AML with MDM2 inhibitors generally combined with chemotherapy, including idasanutlin with so far limited results 34 and HDM201 with very preliminary ones 35 or combined with other molecules i.e., milademetan with quizartinib 36 or azacitidine. 37 MDM4 inhibitors have also been tested in AML in vitro, with very limited in vivo experience.…”
mentioning
confidence: 99%
“…Elevated sirtuins expression has been reported in AML and in other cancers (34) and promotes tumourigenesis and drug resistance (6). Particularly, SIRT1 deacetylates different histone and nonhistone proteins, among them p53, regulating both cell cycle and mitochondrial function (35) and playing a critical role in tumor initiation progression and metastasis (30,36,37). Effects of p53 on regulation of PGC1α, a metabolic modulator in cancer (38,39) have been previously reported (40,41), with p53-mediated PGC1α up-regulation orchestrating antioxidant and metabolic response (42).…”
Section: Discussionmentioning
confidence: 95%
“…Normally, in the case of DNA damage and excessive cellular stress, its expression levels and activation increase in order to stop the cell cycle, allowing DNA repair or entry into apoptosis [48]. However, p53 is mutated or silenced in 50-55% of human cancers [49] and, therefore, it is one of the most widely studied targets in the search for new anticancer compounds. In the present study, in the two cell lines used, p53 was not functional since it presented a nonsense mutation according to the Cancer Cell Line Encyclopedia of the Broad Institute.…”
Section: Discussionmentioning
confidence: 99%